Politeness in Requesting and Refusing within Students' Conversation at SMP Al-Washliyah 24 Medan - Nurhayani (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The purpose of this study is to examine the use of politeness strategies in requesting and refusing within students' conversations at SMP Al-Washliyah 24 Medan, particularly among Generation Z learners in the millennial era. This research adopts a qualitative approach, using interviews and observation as instruments for data collection. The data were analyzed qualitatively to assess how students apply politeness in everyday communication. The findings reveal that students' approaches to learning, discussion styles, and use of learning resources are significantly influenced by their surrounding environment and upbringing. Although students are actively involved in various school-based activities and organizations, a decline in manners and moral values was observed, which is attributed to generational shifts and reduced emphasis on character education. Furthermore, the influence of technological advancement and liberal educational practices appears to shape students’ critical thinking, particularly in adapting to frequent changes in curriculum and learning models.